KETERKAITAN PEMAHAMAN FILSAFAT FISIKA DALAM PEMBELAJARAN FISIKA - Suyan Nicole Lumban Gaol; Khairunnisa Masna Widyatmoko; Rofiah Adaliah; Aldira Lilian Gebiyanti; I ketut Mahardika; Habibah Khusna Baihaqi; Kendid Mahmudi (LPPM Universitas Cipta Mandiri, 2026)
The philosophy of physics is a branch of the philosophy of science that examines the nature of physical reality, the foundations of scientific knowledge, and the values involved in the application of physics. Understanding the philosophy of physics is essential in the process of learning physics, as it helps students comprehend scientific concepts not only mathematically but also conceptually and reflectively. This study aims to explore the relationship between the understanding of the philosophy of physics and the effectiveness of physics learning at the secondary and higher education levels. The method used is a literature study with a qualitative approach. The findings indicate that understanding the philosophy of physics can strengthen critical thinking skills, enhance students’ epistemological awareness, and foster a more reflective scientific attitude toward natural phenomena. Integrating the philosophy of physics into instruction also encourages teachers to emphasize conceptual aspects rather than merely formulas and calculations, making the learning process more meaningful and humanistic.